Insan Kamil as Psychological Ideality in the Thought of Abdul Karim Al-Jilli and its Manifestation in the Prophet Muhammad SAW - Anahdiah, Shofia; Soleh, Achmad Khudori (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
Abdul Karim Al-Jilli, a renowned figure in Sufism, developed the concept of Insan Kamil (the Perfect Human) by referring to the character of the Prophet Muhammad as the ideal example. This study aims to explore and understand Al-Jilli's concept of Insan Kamil in the context of psychology. In this regard, the study examines the concept of Insan Kamil and the emulation of Prophet Muhammad as the most perfect example of a human being. Al-Jilli’s book titled al-Insan al-Kamil fi ma’rifati al-‘Awakhir wa al-‘Awa’il serves as a primary reference for this research, which employs a qualitative descriptive method with data analysis through content analysis. The results of the study reveal several points: (1) According to Al-Jilli, Insan Kamil is a mediator between God (al-Haqq) and humanity (makhluq), a figure capable of connecting the physical world with the spiritual realm. (2) The emergence of Insan Kamil as a Divine manifestation consists of five stages: Uluhiyah, Ahadiyah, Wahidiyah, Rahmaniyah, and Rububiyah. The process for a servant to achieve Insan Kamil passes through three stages: al-Bidayah, al-Tawasuth, and al-Khitam. (3) According to Al-Jilli, Muhammad represents the ideal type for every human, as his being reflects the image of God in the most perfect form and possesses abilities beyond those of ordinary humans, both in terms of personality and knowledge.